Diarrhea Infections in North-Eastern Ukraine: Evolution of Epidemic Process (Bangladesh Journal of Medical Science, 2020)
Background: The significance of some infection sources, pathways of pathogen transmission and etiological structure of diarrhea infections (DI) have changed. Many issues of DI epidemiology are still insufficiently studied, which prevents the organisation of quality epidemiological surveillance and diseases control.Objectives: To study the DI epidemic situation (ES) in North- Eastern Ukraine and to identify the factors that determines the characteristics of epidemic process (EP).Material and Methods: The reports of Ministry of Health of Ukraine (1960- 2018) and Head Statistics Administration of Sumy Oblast (2001-2018) have been used. The biological properties of 40 strains of K. pneumoniae, 50 - S. aureus, 40 - E. cloacae recovered from the feces of patients with DI have been studiedResults: It has been found that the EP of DI is characterized by a sharp decrease in the incidence of typhoid fever and shigellosis, increase in the incidence of salmonellosis and dominance of DI caused by other specified or unspecified pathogens (SDI and UDI) in the nosological structure (p